Presence of Pre-rRNAs before Activation of Polymerase I Transcription in the Building Process of Nucleoli during Early Development of Xenopus laevis - Verheggen, Céline (The Rockefeller University Press, 1998)

(untitled)
During the early development of Xenopus laevis, we followed in individual nuclei the formation of a nucleolus by examining simultaneously its structural organization and its transcriptional competence. Three distinct situations were encountered with different frequencies during development. During the first period of general transcriptional quiescence, the transcription factor UBF of maternal origin, was present in most nuclei at the ribosomal gene loci. In contrast, fibrillarin, a major protein of the processing machinery, was found in multiple prenucleolar bodies (PNBs) whereas nucleolin was dispersed largely in the nucleoplasm. During the second period, for most nuclei these PNBs had fused into two domains where nucleolin concentrated, generating a structure with most features expected from a transcriptionally competent nucleolus. However, RNA polymerase I–dependent transcription was not detected using run-on in situ assays whereas unprocessed ribosomal RNAs were observed. These RNAs were found to derive from a maternal pool. Later, during a third period, an increasing fraction of the nuclei presented RNA polymerase I–dependent transcription. Thus, the structural organization of the nucleolus preceded its transcriptional competence. We conclude that during the early development of X. laevis, the organization of a defined nucleolar structure, is not associated with the transcription process per se but rather with the presence of unprocessed ribosomal RNAs.